Upper bound of fekete-szego determinant for a-close-to-convex functions / Sarah Roslan, Nik Hashimah Rashidee and Nur Nadira Ashyikin Muhammad Fuad Tiew - Roslan, Sarah; Rashidee, Nik Hashimah; Muhammad Fuad Tiew, Nur Nadira Ashyikin (2018)
Every class of functions have their own unique properties, however each class can only be computed by using certain methods hence it has become cumbersome in determining which method is the best suited for which class of functions. The study is conducted to discover new subclass of analytic functions, and find the Fekete-Szego determinant for the new subclass of analytic functions.